Impacts of psychiatric clinical posting on attitudes towards psychiatry, mental illness, career choices, and help-seeking intentions: a mixed-methods study among nursing students in ebonyi state, Nigeria - Stanley, Njaka (2025)
Negative perceptions of mental illness and psychiatry persist globally, especially among healthcare professionals and students. Studies showed increasing stigma and declining interest in psychiatry as a career among health students. This mixed-method study evaluates the impact of clinical psychiatry postings on nursing students' attitudes towards psychiatry, career choices and help-seeking intentions in Ebonyi State, Nigeria. The quantitative phase employed standardized scales (ATP-18, MICA4 and GHSQ) in pre and post-test assessment of 400 students. The qualitative phase involved semi-structured interviews with 12 purposively sampled participants. Data analysis utilized SPSS version 26 for quantitative data and NVivo version 10 for qualitative themes. Results demonstrated a statistically significant improvement in attitudes towards psychiatry (p<0.001), mental illness (p<0.001) and help-seeking intentions (p<0.001), though career choice in psychiatry remained unchanged (p=0.653). Marital status (p=0.002) and school of the respondents (p<0.001) were significantly associated with attitudes towards psychiatry. In contrast, attitudes towards mental illness had significant associations with school (p<0.001), gender (p=0.031) and family income (p=0.01). The primary determinants of a career choice in psychiatry included job satisfaction (p<0.001), interest in psychiatry (p=0.044), family influence (p=0.013) and interest in community services (p=0.014). Additionally, factors influencing help-seeking intentions for mental disorders were school (p<0.001), level of study (p<0.001) and exposure to psychiatry lectures (p<0.001). The qualitative phase of the study revealed that the student’s experiences in posting had three themes (posting was interesting, posting was educative, posting was a tedious experience). Their views on psychiatry and mental illness formed three themes (Nature of psychiatry, behaviour of mental health professionals and Nature of care setting) while career choices and help-seeking intentions were influenced by the themes (behaviour of mental health professionals, nature of psychiatry, educational exposure and Interest. This study concluded that clinical psychiatry postings positively impact attitudes towards psychiatry, mental illness and help-seeking intentions. Therefore, it provides valuable insights for improving mental health education and reducing stigma, with implications for addressing workforce challenges in psychiatry.